PEMENUHAN HAK DAN KEWAJIBAN SUAMI ISTRI MEWUJUDKAN RUMAH TANGGA SAKINAH: - Bastiar, Bastiar (State of Islamic Institute Langsa, 2018)
In Islamic law, a marriage contract is not only a civil matter but also a very strong sacred bond that is worth of worship. Therefore, marriage must be maintained properly to realize the sakinah mawaddah wa rahmah family, but when it is in a sacred bond, there are some couples who are reluctant to fulfill their responsibilities and demand right that are not theirs so that the sakinah family will be difficult to be actualized. This study aimed to determine the understanding of husband and wife about rights and responbilities, and a significant relationship between the rights and obligations acomplishment of husband and wife in realizing a harmonious marriage or sakinah family. This research was normative-empirical legal research in the form of analytical prescriptive which was supported by primary and secondary data. Data collection was obtained through library research, documentation, interviews, and observation. Based on the research was conducted, it found the results: First, husband and wife understand that the position of wife and husband in the household are the same, but they have different rights and obligations, although on the other hand the community understands that the position of the wife in the family is under the husband, they understand it from fiqh salf which states that the wife must uphold her husband with an honor and glory. Second, the concept of Islamic marriage teaches that the rights possessed by husband and wife are balanced with the obligations burdened on them, a husband or wife has balanced obligations. Third, to build a harmonious, peace and peaceful family, they can be performed with developing the Islamic teachings, fostering the mutual respect, coaching the efficient living attitudes, and training a self-awareness from each married couples. Key Words: Fulfillment, Rights and Responbilities, Husband and Wife, Sakinah Household. Abstrak: Dalam hukum Islam akad perkawinan bukan hanya perkara perdata semata, melainkan juga ikatan suci yang sangat kokoh yang bernilai ibadah. Untuk itu perkawinan harus dipelihara dengan baik sehingga akan terwujudnya keluarga sakinah mawaddah wa rahmah, namun ketika telah berada dalam ikatan suci, ada pasangan yang enggan memenuhi kewajiban dan penuntutan hak yang diluar haknya maka keluarga sakinah sebagaimana harapan akan sulit terealisasi. Penelitian ini bertujuan untuk mengetahui pemahaman pasangan suami istri tentang hak dan kewajiban suami istri, dan hubungan yang signifikan antara pemenuhan hak dan kewajiban suami isteri dalam mewujudkan perkawinan yang harmonis atau perwujudan keluarga sakinah. Penelitian ini adalah penelitian hukum normatif-empiris dalam bentuk preskriptif analitis yang didukung oleh data primer dan sekunder. Pengumpulan data melalui studi pustaka, dokumentasi, wawancara, dan observasi. Berdasarkan penelitian yang dilakukan ditemukan hasil: Pertama, Suami istri memahami bahwa kedudukan istri dan suami dalam rumah tangga sama, namun memiliki hak dan kewajiban yang berbeda, meskipun disisi lain masyarakat memahami bahwa kedudukan istri dalam keluarga berada di bawah suami, hal ini mereka pahami dari pemahaman fikih salaf yang menyebutkan bahwa istri harus menjunjung tinggi suaminya dengan kehormatan dan kemuliaan. Kedua, Konsep pekawinan Islam mengajarkan bahwa hak-hak yang dimiliki oleh suami maupun isteri adalah seimbang dengan kewajiban yang dibebankan kepada mereka,seorang suami atau isteri memiliki kewajiban-kewajiban yang seimbang. Ketiga, untuk mewujufkan keluarga yang harmonis, sakinah dan penuh kedamaian dapat di lakukan dengan cara Pembinaan penghayatan ajaran agama Islam, Pembinaan sikap saling menghormati, Pembinaan sikap Hidup Efisien, dan Pembinaan sikap suka mawas diri dari masing-masing pasangan suami isteri. Kata Kunci: Pemenuhan, Hak dan Kewajiban, Suami Istri, Rumah Tangga